IMPLEMENTASI PEMBELAJARAN KONSEP BILANGAN DALAM MENGEMBANGKAN KEMAMPUAN BERHITUNG ANAK KELOMPOK B MELALUI BERMAIN JENGA ANGKA - Tjutju Djuariah; Agus Hasbi Noor; Sharina Munggaraning Westhisi (IKIP Siliwangi, 2022)
This research is motivated by the fact in the field that the ability to count in the introduction of the concept of numbers in group B children at the Mawar Sari PAUD Post is still low due to the selection of learning methods that are less interesting and boring. Learning by playing using the jenga numbers game is one of the learning methods chosen in developing the numeracy skills of group B children at Mawar Sari PAUD. This study aims to describe the implementation of number concept learning by playing jenga numbers activities in developing children's numeracy skills and children's responses in learning. The research method used was descriptive qualitative method with the research subjects being 15 children in group B PAUD Mawar Sari. Collecting data through observation, interviews and documentation. Data analysis in the form of data reduction activities, data display and drawing conclusions. The results showed that the introduction of the concept of numbers in the development of children's numeracy skills developed in meetings one to eight with good planning according to the RPPH, so that children were able to name and show numbers 1-10, sorting the numbers from the smallest and largest 1-10, adding up the numbers 1 -10 well due to the stimulation provided by the teacher in learning using jenga numbers, children are very happy, excited and enthusiastic in learning because it is supported by fun media.